Pembelajaran Keterampilan Menulis (Maharah al-Kitabah) dalam Bahasa Arab - Munawarah Munawarah; Zulkiflih Zulkiflih (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
Writing skill (maharah al-kitabah) is the highest skill of the four language skills. Writing is an activity that has a relationship with thought processes and expression skills in the form of writing. Judging from the aspect of Arabic proficiency, writing can be said to be a very complex activity, because it requires the ability to organize and organize ideas coherently and logically, as well as the ability to present writing in a variety of written languages and different writing rules. This writing activity is difficult for students, because it requires several skills, namely skills in forming letters and mastering spelling and the skills to generate thoughts and feelings in the form of Arabic writing. Therefore, it is necessary to understand the objectives and principles of learning writing skills and writing skills learning techniques to help students understand the material and achieve the goals of learning writing skills (Maharah al-kitabah). This paper tries to explain the theory of learning writing skills scientifically which includes the understanding of writing skills (maharah al-kitabah), the objectives of learning writing skills (maharah al-kitabah), the principles of learning writing skills (maharah al-kitabah) and skills learning techniques. write (maharah al-kitabah) in Arabic.